DETERMINAN KEPUTUSAN PEKERJA USIA MUDA BEKERJA PADA SEKTOR PERTANIAN DAN NON-PERTANIAN (STUDI PADA PROVINSI JAWA TIMUR) - Shabri Mulyawan, Rafi; Moh. Athoillah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Structural transformation of the economy from traditional to modern systems will also be followed by massive structural migration of the workforce. The lack of innovation and added value in the agricultural sector has reduced the interest of young workers to work in the agricultural sector. The reform era caused the position of the agricultural sector as the basis sector in the Indonesian economy to be replaced by the non-agricultural sector which caused the paradigm of national economic development to change. East Java as one of the provinces with a large contribution to agriculture in Indonesia has also experienced a decline in terms of workforce in the agricultural sector. This study attempts to detect the determinants that impact on the workforce's decision to work in the agricultural or non-agricultural sectors. Using data from the National Labor Force Survey (SAKERNAS) from 38 districts/cities in East Java Province and using the Logit Regression analysis method, this study found that all the variables in the model have a significant influence on the decision to work in the agricultural and non-agricultural sectors.